Mental distress along the cascade of care in managing hypertension - Ang, Chiew Way; Tan, Min Min; Bärnighausen, Till; Reininghaus, Ulrich; Reidpath, Daniel; Su, Tin Tin (Scientific reports, 2022)
Hypertension might be a contributing factor of mental illness. The aim of this study was to investigate the association between different levels of hypertension care and mental distress among hypertensive individuals in Malaysia. We constructed a hypertension care cascade using data of 6531 hypertensive individuals aged ≥ 35 years that were collected as part of the community health survey conducted in 2013 in the South East Asia Community Observatory. We examined the association between the status of hypertension care and mental distress using multiple logistic regressions. Respondents who had not been screened for hypertension and those who had uncontrolled blood pressure (BP) had higher odds of depression, anxiety and, stress compared to those who had been screened and those who had controlled BP, respectively. Respondents who were not taking antihypertensive medication had lower odds of depression and anxiety compared to those who were on medication. There was an association between different levels of hypertension care and mental distress. The application of a hypertension care cascade may help improve the provision of mental health support in primary care clinics. Specific mental health interventions could be provided for patients with particular needs along the cascade.